Separate Recording of A-delta and C Fiber-Mediated Nociceptive Flexor Reflex Responses of Mouse Hindlimb Using Electromyography and the Characteristics of Wind-Up Appearing in the Responses - Satoko Kimura; Hitoshi Kontani (Elsevier, 2008)
To measure separately electromyogram (EMG) activity of A-delta and C fiber- mediated responses and study the characteristics of drug effects on them in mice, we modified our original method designed to measure these responses associated with hindlimb withdrawal movements. Single electrical stimulation applied to the toe elicited biphasic EMG activity in the ipsilateral femoris biceps muscle and withdrawal movement. Times to peak of the short- and long-latency response of EMG activity were almost consistent with those obtained from the hindlimb movement. As the short- and the long-latency responses of EMG activity were selectively inhibited by tetrodotoxin (TTX) (3 and 10 μM) and capsaicin (0.98 and 3. 27 mM) applied to the sciatic nerve, the responses were considered to occur via A-delta and C fibers, respectively. A 0.5-Hz repetitive conditioning stimulus (CS) elicited significant wind-up in both the A-delta and C fiber-mediated responses. The wind-up of the A-delta fiber-mediated response disappeared during the CS and that of the C fiber-mediated response continued throughout the CS. This method is simple but useful for studying the effect of analgesic agents on A-delta and C fiber-mediated nociceptive responses and clarifying the roles of these afferent fibers in chronic pain in mice. Keywords:: nociceptive flexor reflex, A-delta fiber, C fiber, wind-up, electromyogram